2013
DOI: 10.1111/1469-0691.12232
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella pneumoniae harbouring OXA-48 carbapenemase in a Libyan refugee in Italy

Abstract: A carbapenem-resistant Klebsiella pneumoniae was isolated from a blood-culture of an inpatient from Libya, hospitalized in the intensive-care unit of Negrar Hospital, Italy. The clinical isolate carried the following β-lactamase genes, bla(TEM -1), bla(SHV -11), bla(OXA -1), bla(CTX -M-15) and bla(OXA -48), respectively. The bla(OXA -48) gene was inserted in the Tn1999.2 transposon type, carried on a conjugative, 60-kilobase plasmid, that presented an L/M backbone, hosted by a multidrug-resistant ST 101 K. pne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…On the other hand, carbapenemase genes different from bla KPC have so far been considered less of a problem, whose magnitude has perhaps not been fully assessed, with only sporadic reports being published (Gaibani et al, 2013;Kocsis et al, 2013). As an example, although VIM carbapenemase was firstly recognized in Italy (Lauretti et al, 1999), the exact magnitude of its distribution in our country is still difficult to establish.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, carbapenemase genes different from bla KPC have so far been considered less of a problem, whose magnitude has perhaps not been fully assessed, with only sporadic reports being published (Gaibani et al, 2013;Kocsis et al, 2013). As an example, although VIM carbapenemase was firstly recognized in Italy (Lauretti et al, 1999), the exact magnitude of its distribution in our country is still difficult to establish.…”
Section: Discussionmentioning
confidence: 98%
“…3). In Africa, they have been mainly identified in the northern countries (Morocco, Algeria, Tunisia, Egypt, and Libya) [101,[115][116][117][118][119][120][121][122][123][124][125][126], but OXA-48 producers have also been identified in Senegal and South Africa [127,128] (Fig. 3).…”
Section: Thementioning
confidence: 99%
“…However, three studies reported the presence of OXA-48-producing K. pneumoniae isolated from Libyan patients transferred to Europe for treatment. Indeed, Kocsis et al reported that a carbapenem-resistant K. pneumoniae carrying the blaOXA-48 gene was recovered from the blood culture of a Libyan patient hospitalized in the ICU of the Sacro Cuore-Don Calabria Hospital in Negrar, Italy [38]. Italy is the country with the highest incidence of OXA-48-producing K. pneumoniae isolates, and has been considered to be the epicenter of the spread of this enzyme in Mediterranean basin [39].…”
Section: Indeed Mamlouk Et Al Detected the Blactx-m-15 Gene Inmentioning
confidence: 99%